2016
DOI: 10.3389/fmicb.2016.01698
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Stress Resistances of Clostridium difficile Spores and Vegetative Cells

Abstract: Clostridium difficile is a Gram-positive, sporogenic and anaerobic bacterium that causes a potentially fatal colitis. C. difficile enters the body as dormant spores that germinate in the colon to form vegetative cells that secrete toxins and cause the symptoms of infection. During transit through the intestine, some vegetative cells transform into spores, which are more resistant to killing by environmental insults than the vegetative cells. Understanding the inherent resistance properties of the vegetative an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(97 citation statements)
references
References 84 publications
2
93
0
2
Order By: Relevance
“…We found that only the first dilutions of the R20291 strain grew in the presence of 0.4% or 0.1% of O 2 as compared to the growth of all dilutions of the 630Δ erm strain. This result suggesting that the R20291 strain was more sensitive to O 2 than the 630Δ erm strain is consistent with recent studies (Edwards et al ., ). In addition, the complemented strain in the R20291 genetic background showed higher tolerance to O 2 than the parental strain did at 0.1% and 0.4% of O 2 .…”
Section: Resultsmentioning
confidence: 97%
“…We found that only the first dilutions of the R20291 strain grew in the presence of 0.4% or 0.1% of O 2 as compared to the growth of all dilutions of the 630Δ erm strain. This result suggesting that the R20291 strain was more sensitive to O 2 than the 630Δ erm strain is consistent with recent studies (Edwards et al ., ). In addition, the complemented strain in the R20291 genetic background showed higher tolerance to O 2 than the parental strain did at 0.1% and 0.4% of O 2 .…”
Section: Resultsmentioning
confidence: 97%
“…A minimum of three biological replicates were performed for each growth curve shown. The pH of cultures and solutions was measured as previously described (Edwards et al, 2016b).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were harvested by centrifugation, resuspended in SDS-PAGE loading buffer (without dye) and mechanically disrupted as previously described (Edwards et al, 2016a;Nawrocki et al, 2016). The pH of the cultures were also measured at the time of harvest, as previously described (Edwards et al, 2016b). Protein concentrations were assessed using a micro BCA assay (Thermo Scientific) and 8 mg of whole cell protein loaded onto a 12% polyacrylamide gel.…”
Section: Western Blots and Ph Assessmentmentioning
confidence: 99%
“…Spores are also produced in the gut and cause both spreading into the environment and relapse (Deakin et al, 2012;Janoir et al, 2013). The resistance to extreme environmental conditions and chemical compounds, including oxygen, antibiotics and disinfectants, makes the spores difficult to eradicate (Rupnik et al, 2009;Edwards et al, 2016).…”
Section: Introductionmentioning
confidence: 99%